Globalization and Sustainability A Humanist Agenda - Witoszek, Nina 1954- (2006)
At the core of this contribution are two questions: 1) Is the vision of sustainable development not just ethically justified and economically viable—but captivating enough to clean poisoned wells and restore the structures of the mind? 2) Is the current religious revival in non-European countries a possible ally—or adversary—of positive globalization? The argument is that among the greatest obstacles to the endeavour of sustainable development is human attraction to stories of excess, profusion, decadence, a sense of ending or shock. People are compelled by the myths of transgression, irreverence, and the hedonist greatness and glory in the same way that they are not drawn to the penitential story of renewable resources, equal distribution. Economic reason and democratic Geist—have either devalued or suppressed human desire for transcendence or muddled values. Those who attempt to renew the environmental narrative through the romance with Eastern spirituality or via the alterglobalist protest are often either unwitting allies of neoliberal order or lack any coherent plan or vision of the future. The much flaunted ‘postmodern’ mindset is of little use, since it has celebrated the lack of assurance and conviction, and thus launched a quixotic project of founding the social and cultural values on the lack of foundations themselves. The suggestion is that the search for the solid ground should start, not just from reclaiming the commons but, first of all, from reclaiming the humanist project, which has been lost by Western civilization.
Keywords: Consumers; Globalization; Humanism; Sustainability